Technological advances in integrating multi-kilobase DNA sequences into genomes. (September 2018) - Gurumurthy, Channabasavaiah B.; Perez-Pinera, Pablo
Abstract: Genetic engineering, enabled by rapid advances in programmable nucleases, is rapidly transforming science and society. Notably, despite remarkable progress developing more effective and specific technologies for introducing double strand-breaks in genomic DNA, a large number of potential applications require DNA integration rather than introduction of stochastic mutations. Integration of heterologous DNA has been traditionally accomplished through manipulation of DNA repair mechanisms to favor homologous recombination. However, gene editing applications that rely on homologous recombination are limited by its ineffectiveness for integrating large segments of DNA. Recent advances in genetic engineering have improved the efficiency of homologous recombination and also have identified alternative DNA repair pathways that can be hijacked to accomplish targeted DNA integration. These methods have been utilized to integrate DNA in excess of 200 Kb in size, which marks the dawn of a new era in gene therapy, humanization of animal models, and even re-writing human genomes. Highlights: Programmable nucleases enable targeted integration through introduction of targeted double-strand breaks in genomic DNA. Multiple DNA repair pathways can be exploited to optimize parameters that impact the outcome of the integration of large DNA. Engineering of recombinases, transposases and viral systems can overcome some limitations inherent to programmable nucleases. Multiple safety concerns must be addressed to avoid regulatory hurdles.